Stosunki między państwem i biznesem a wzrost gospodarki - Ząbkowicz, Anna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
The article presents an approach to government-business relations which differs from a conventional perspective. The main stream of political science as well as the mainstream economics agree that business should be separated from the government. The article reveals that the concept of „business” is not homogenous and, accordingly, analyzes its five aspects. It shows the conditions under which collaboration between the government officials and businessmen needs not be harmful for economic growth, and may be even conducive to it. Examples in the article show that cooperation between government and business may be more beneficial than building barriers between them.